OPTIMALISASI PREMI ASURANSI RETAIL ELEKTRONIK MELALUI INOVASI EKOSISTEM DIGITAL TERINTEGRASI DI INDONESIA - Reimond Hasangapan Mikkael Napitupulu; R. Muh. Deddy Hanif Sardjito; Pambudi Nugroho; Wahyu Maulana (POLITEKNIK LP3I JAKARTA, 2025)
The development of digital technology has driven significant transformation in the insurance industry, especially in the electronic retail insurance segment. This study aims to examine how integrated digital ecosystem innovation can optimize electronic retail insurance premiums in Indonesia. Using the action research method with the DMADV lean six sigma approach, this study involved in-depth interviews with industry players, including insurance companies, digital platforms, and regulators. The results of the study show that the integration between platforms, digital payments, and application-based insurance services creates an ecosystem that strengthens operational efficiency, expands consumer access, and enables more competitive and risk-adaptive premium determination. In addition, the use of real-time customer data allows for more targeted personalization of insurance products and services. This study emphasizes the importance of cross-sector collaboration in building a digital ecosystem that supports the sustainable growth of electronic retail insurance in Indonesia.